1995
DOI: 10.1128/aem.61.6.2302-2307.1995
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the robA gene increases organic solvent tolerance and multiple antibiotic and heavy metal ion resistance in Escherichia coli

Abstract: Escherichia coli K-12 OST3410 was isolated previously as a stable cyclohexane-tolerant mutant derived from cyclohexane-sensitive strain JA300. A plasmid which provides cyclohexane tolerance to strain JA300 was isolated from the OST3410 genomic library. Subcloning and sequence analysis showed that the plasmid contained the robA gene, whose gene product was reported to bind specifically to the right border of oriC. We observed that the robA gene on the multicopy plasmid generally increased the organic solvent to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(65 citation statements)
references
References 26 publications
1
64
0
Order By: Relevance
“…In an earlier study salicylate was reported to be capable of activating marRAB via rob [28]. It has also been reported that the overexpression of rob exhibits resistance against antibiotics, organic solvents and superoxide-generating agents through plasmid [16,29]. In this study strong correlations between overexpression of rob and carbapenem resistance was observed when exposed to concentration gradient meropenem stress which is not being reported earlier.…”
Section: Discussionmentioning
confidence: 44%
“…In an earlier study salicylate was reported to be capable of activating marRAB via rob [28]. It has also been reported that the overexpression of rob exhibits resistance against antibiotics, organic solvents and superoxide-generating agents through plasmid [16,29]. In this study strong correlations between overexpression of rob and carbapenem resistance was observed when exposed to concentration gradient meropenem stress which is not being reported earlier.…”
Section: Discussionmentioning
confidence: 44%
“…The mechanism of induction of acrAB by bile acids and fatty acids is not known. Interestingly, the overproduction of yet another member of the AraC/XylS family, Rob, is known to increase resistance (Ariza et al ., 1995;Nakajima et al ., 1995;Lee et al ., 1996), presumably through increased production of the AcrAB pump (Jair et al ., 1996;White et al ., 1997). Rob is constitutively present at very high concentrations (Skarstad et al ., 1993;Kakeda et al ., 1995), and these overproduction experiments are unlikely to reflect physiological regulatory mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In Escherichia coli, the induction of a common set of < 16 genes (acnA,acrAB,fldA,fpr,fumC,inaA,mar,micF,nfo,nfsA,poxB,ribA,sodA,tolC and zwf) confers tolerance to organic solvents, resistance to a variety of antibiotics and heavy metals and combats the oxidative stress imposed by redox-cycling compounds such as paraquat (Nakajima et al, 1995;Demple, 1996;Alekshun and Levy, 1997). Three distinct regulatory systems can stimulate the expression of these genes, with the direct transcriptional activators of each system being the highly related proteins SoxS, MarA and Rob, which comprise a subgroup of the AraC/XylS family of bacterial regulatory proteins (Gallegos et al, 1997).…”
Section: Introductionmentioning
confidence: 99%